The influence of different training systems and rootstocks on 'Sauvignon Blanc' grapes - Simonetti, Lilian Massaro [UNESP]; Sousa, Marilia Caixeta [UNESP]; Moura, Mara Fernandes; Silva Nunes, Jesion Geibel da [UNESP]; Diamante, Marla Silvia [UNESP]; Silva, Monica Bartira da [UNESP]; Rodrigues da Silva, Marlon Jocimar [UNESP]; Callili, Daniel [UNESP]; Pereira Lima, Giuseppina Pace [UNESP]; Tecchio, Marco Antonio [UNESP] (Inst Agronomico, 2021)
In viticulture, training systems and rootstocks are crucial factors in the growth and development of plants, thus affecting the production and quality of grapes. Therefore, the present study aimed to determine the best combination of rootstock and training system for 'Sauvignon Blanc', in Jundiai, state of Sao Paulo, Brazil. To assess the data, a randomized block design in a 2 x 2 factorial scheme was used, that is, two rootstocks ('IAC 766 Campinas' and '106-8 Mgt') and two training systems (low and high espaliers), with four replications. The characteristics assessed were production, physicochemical analysis and concentration of bioactive compounds. With regard to the physicochemical composition of the grape must, the results indicated that the tested combinations are within the standard requirements for the winemaking industry; outcomes may change according to the rootstock used, i.e., an increase in production or an increase in the nutritional quality of the fruits. Nevertheless, '106-8 Mgt' rootstock showed great yield in both training systems, that is, an increase of up to 80%. Finally, 'Sauvignon Blanc' must be grafted on to 'IAC 766 Campinas' rootstock through a low espalier system to achieve a high content of phenolic compounds and flavonoids, and high antioxidant activity.
Keywords: bioactive compounds; antioxidant capacity; yield; '106-8 Mgt'; 'IAC 766'